(untitled) (Research, Society and Development, 2020)
Ketchup is a popular sauce in several countries, characterized by its strong color, sweet taste and thick consistency. Variations in these characteristics can interfere with the acceptance of the product, thus, the objective of this study was to analyze the acceptance of sensory parameters (aroma, color, flavor, appearance) and purchase intention of ketchup added with pitomba starch and therefore compare with the sensory attributes of ketchup added with commercial corn starch. Starch extraction was performed by crushing the pitomba seed in sodium metabisulfite solution (0.2%) followed by drying at 50 ° C. The ketchups were formulated with the addition of 0.5 and 1% pitomba starch, 0.5 and 1% corn starch, and a control formulation. The formulations were evaluated microbiologically for thermotolerant coliforms and Salmonella and submitted to evaluation of sensory acceptance regarding the parameters of color, appearance, aroma, flavor and purchase intention. The results revealed that the formulations presented a good microbiological pattern and that the ketchups did not show significant difference (p ≤ 0.05) between the parameters of color, appearance, aroma and flavor, indicating that the percentages and types of starch used did not cause interference in the sensory characteristics evaluated. The greatest purchase intentions were recorded for formulations with added starches, suggesting consumers’ preference for consistent formulations.